2019
DOI: 10.1371/journal.pone.0221346
|View full text |Cite
|
Sign up to set email alerts
|

General versus sports-specific injury prevention programs in athletes: A systematic review on the effects on performance

Abstract: Introduction Injury prevention programs (IPPs) are an inherent part of training in recreational and professional sports. Providing performance-enhancing benefits in addition to injury prevention may help adjust coaches and athletes’ attitudes towards implementation of injury prevention into daily routine. Conventional thinking by players and coaches alike seems to suggest that IPPs need to be specific to one’s sport to allow for performance enhancement. The systematic literature review aims to fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Typically, exercise-based injury prevention programmes aim at improving athletes’ neuromuscular and proprioceptive performance ( Mandelbaum et al, 2005 ). Effective prevention, however, should be based on sport- and age-specific programmes that consider the epidemiology, mechanisms, and contextual factors of the injuries of the athletes to be protected ( van Mechelen et al, 1992 ; Sugimoto et al, 2016 ; Plummer et al, 2019 ). Accordingly, real-world implementation factors should already be taken into consideration in both the development and evaluation phases of sports injury prevention programmes ( Bolling et al, 2018 ; O’brien et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, exercise-based injury prevention programmes aim at improving athletes’ neuromuscular and proprioceptive performance ( Mandelbaum et al, 2005 ). Effective prevention, however, should be based on sport- and age-specific programmes that consider the epidemiology, mechanisms, and contextual factors of the injuries of the athletes to be protected ( van Mechelen et al, 1992 ; Sugimoto et al, 2016 ; Plummer et al, 2019 ). Accordingly, real-world implementation factors should already be taken into consideration in both the development and evaluation phases of sports injury prevention programmes ( Bolling et al, 2018 ; O’brien et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huang et al identified that IPPs targeting ACL injuries could reduce these injury rates by 53% (Huang et al, 2020). However, it should be noted that the way these IPPs are constructed and implemented plays a significant role in its effectiveness (Plummer et al, 2019;Webster & Hewett, 2018;Wiggins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number of injuries affecting boxers' performance and their absenteeism often increased, in addition to the high cost of their treatment. A recently published systematic review reported that sports-specific injury prevention programs strongly influence most performance indices and result in large-scale improvements to balance (66%), power (83%), strength (75%), and speed/agility (62%) [27]. These findings reinforce the importance of implementing an injury prevention exercise program among boxers, which could reduce injuries and their consequences.…”
Section: Discussionmentioning
confidence: 73%